Trabalho artesanal e trabalho industrial como elementos de sociabilidade, subjetividade e tragédia em “A mão esquerda”, de Roniwalter Jatobá - Angela Maria Rubel Fanini; Adriana Cabral dos Santos (Estudos de Literatura Brasileira Contemporânea)
This paper investigates the short story “A mão esquerda”, by the Brazilian writer Roniwalter Jatobá, focusing the handy craft labor as an element of subjectiveness, sociability and ontology and factory labor as an element of depersonalization, disagregation and tragedy. The study backgrounds on Bakhtin’s theory on the novel and on Engels’ (1990) and Lukács’ (1980) view on human labor, analyzing language, point of view, space, intertextuality and social context.